A new CUL4B variant associated with a mild phenotype and an exceptional pattern of leukoencephalopathy. Issue 10 (17th August 2017) - Weissbach, Susann; Reinert, Marie‐Christine; Altmüller, Janine; Krätzner, Ralph; Thiele, Holger; Rosenbaum, Thorsten; Nürnberg, Peter; Gärtner, Jutta
Abstract : Cabezas type of X‐linked syndromic intellectual disability (MRXSC; MIM300354) is a rare X‐linked recessive intellectual disability characterized primarily by intellectual disability, short stature, hypogonadism, and gait abnormalities. It is caused by a wide spectrum of hemizygous variants in CUL4B . In a 10‐year‐old boy with an exceptional leukoencephalopathy pattern, we identified a new missense variant p.Leu329Gln in CUL4B using "Mendeliome" sequencing. However, his phenotype does not include the severe characteristics currently known for MRXSC. We discuss the divergent phenotype and propose a potential connection between the different CUL4B variants and corresponding phenotypes in the context of the current literature as well as 3D homology modeling.